Presence of Fusarium graminearum sensu stricto associated with triticale (× Triticosecale Wittmack) in Argentina - Dinolfo, María Inés (2020)
Aim of study: To report the occurrence of Fusarium graminearum sensu stricto (s.s.) on triticale grains from field samples in Argentina and the potential mycotoxin production for these isolates. Area of study: Buenos Aires province, Argentina Material and methods: A total of 40 samples from different crops (barley, rye, triticale, and wheat) showing Fusarium head blight symptoms were taken during 2017/2018 harvest season. Colonies with colour and mycelium similar to Fusarium were taken and were morphologically and molecularly identified. The potential to produce deoxynivalenol, 15-acetyl deoxynivalenol and zearalenones was determined. Also, the Koch´s postulates were used to evaluate the pathogenic capacity of the F. graminearum s.s. isolates in triticale. Main results: Two Fusarium isolates were identified morphologically as F. graminearum, which were confirmed molecularly by PCR using the specific Fg16 F/R primers pair and by sequencing red and tri101 genes. The sequences obtained were compared with those available in the NCBI database using BLAST tools, showing 99-100% homology with those belonging to F. graminearum s.s. The results demonstrated that F. graminearum s.s. isolates were pathogenic when triticale spikes were inoculated by spraying under greenhouse conditions. Research highlights: To our knowledge, this is the first time that the presence of F. graminearum s.s. is reported associated with triticale in Argentina.